Answer: h + 245 = new building height (x)
Step-by-step explanation: Since the new building is 245 feet taller than the clock tower, adding the clock tower (h) and 245 feet, will find you the height of the new building
2.if the tank in a car holds 15 gallons of gasoline, the volume of the tank is one cubic foot
3.two cones have equal height. if the base of one cone is a circle and the base of the other cone is a square, the two cones cannot have equal volumes
4.the diameter of the moon is approximately one-fourth the diameter of earth, hence the volume of the moon is one-fourth the volume of earth.
each of these questions are true or false.. could use the help tonight please
Answer:
1. True
2. False
3. False
4. False
Step-by-step explanation:
1. It is true because12 inch is equal to 1 feet, so the area of each side of the cube is 1 square feet, adding the 6 sides of the cube you have a surface area of 6 square feet.
2. It is false because 7.5 gallons is equal to 1 cubic foot.
3. It is true because both cones have equal height but the fact that the bases are different make the volume different.
4. Is false because when you calculate the volume of a sphere you have to raise the radius (half the diameter) to the cube, so there is not a direct relation.
(1)f(x) = x² - 4x + 2, g(x) = 3x - 7
(f o g) (x) = f(g(x)) = f (3x - 7)
= (3x - 7)² - 4(3x - 7) + 2
= (9x² - 42x + 49) + (-12x + 28) + 2
= 9x² - 57x + 79
(2)g(x) = -6x + 5, h(x) = -9x - 11
(g o h) (x) = g(h(x)) = g (-9x - 11)
= -6(-9x - 11) + 5
= 54x + 66 + 5
= 54x + 71
(3)f(x) = √(2x - 5), g(x) = 5x² - 3
(g o f) (x) = g(f(x)) = g(√(2x - 5))
= 5 (√(2x - 5))² - 3
= 5 (2x - 5) - 3
= 10x - 25 - 3
= 10x - 28
x^2 + 3x - 28/ x^2 - 7x + 12
Show your work.
Answer:
(x^4 + -4 x^3 + 12 x^2 - 28)/x^2
Step-by-step explanation:
Simplify the following:
x^2 + 3 x - 7 x + 12 - 28/x^2
Put each term in x^2 + 3 x - 7 x + 12 - 28/x^2 over the common denominator x^2: x^2 + 3 x - 7 x + 12 - 28/x^2 = x^4/x^2 + (3 x^3)/x^2 - (7 x^3)/x^2 + (12 x^2)/x^2 - 28/x^2:
x^4/x^2 + (3 x^3)/x^2 - (7 x^3)/x^2 + (12 x^2)/x^2 - 28/x^2
x^4/x^2 + (3 x^3)/x^2 - (7 x^3)/x^2 + (12 x^2)/x^2 - 28/x^2 = (x^4 + 3 x^3 - 7 x^3 + 12 x^2 - 28)/x^2:
(x^4 + 3 x^3 - 7 x^3 + 12 x^2 - 28)/x^2
Grouping like terms, x^4 + 3 x^3 - 7 x^3 + 12 x^2 - 28 = x^4 + (3 x^3 - 7 x^3) + 12 x^2 - 28:
(x^4 + (3 x^3 - 7 x^3) + 12 x^2 - 28)/x^2
3 x^3 - 7 x^3 = -4 x^3:
Answer: (x^4 + -4 x^3 + 12 x^2 - 28)/x^2
A. q = -2/3p
B. q = -3/2p
C. p = -2/3q
D. p = -3/2q